Premature degradation of poly(α-hydroxyesters) during thermal processing of Bioglass® containing composites - Blaker, Jonny J.; Bismarck, Alexander; Boccaccini, Aldo R.; Young, Anne M.; Nazhat, Showan N. (Acta Biomaterialia, 2010)
Bioactive, biodegradable composites are increasingly being explored as bone replacement materials and as scaffolds for tissue engineering. Their properties are not only dependent on the properties of the filler and matrix, but are also determined by their interaction. This study investigated the effect on poly(d,l-lactide) (PDLLA) matrix when processed at high-temperatures in the presence of Bioglass® particulate filler. Composites with different filler contents were compounded at elevated temperatures by co-extrusion followed by compression moulding and compared with composites of similar composition prepared by thermally induced phase separation (TIPS), a low-temperature processing route. It was found that the inclusion of Bioglass® in PDLLA under elevated temperatures resulted in the degradation of the matrix, leading to a reduction in the mechanical properties of the composites and in the molecular weight of the matrix. Attenuated total reflection Fourier transform infrared (ATR-FTIR) spectroscopy showed the presence of a peak at 1600 cm-1 in the composite material, particularly when processed at elevated temperatures, whereas no peak at this wavelength was discernible for the pure PDLLA. Furthermore, time-based ATR-FTIR spectra taken at elevated temperatures on the TIPS-processed composites showed an increase in the intensity of the peak at 1600 cm-1 and a concomitant reduction of the Cdouble bond, longO stretch peak at 1745 cm-1 with time. This suggested the formation of a carboxylate salt by-products as a consequence of a reaction at the interface between the Bioglass® filler and the PDLLA matrix. Therefore, the results confirmed that this degradation was not solely due to shear effects during the extrusion process. This work thereby supports the assertion that, in the presence of Bioglass® filler particles, poly(α-hydroxyester)-based composites should not be processed at elevated temperatures. © 2009 Acta Materialia In
UnivIS-Import:2015-03-09:Pub.2010.tech.IW.LM.premat
Keywords: Bioactive glass; Biodegradable composite; Bioglass; Scaffolds; Silica